Practical Research on the Evaluation of College English Smart Exam - Yang, Furong (Transactions on Social Science, Education and Humanities Research, 2024)
With the development of technology, the way of network education has also entered the college English teaching, into the classroom teaching. Network education provides rich resources for teaching, providing a new teaching method. While teachers and students enjoy this new form of teaching, network education also puts forward new problems for teaching: how to quickly and accurately find the problems of students in the learning process, and how to carry out more effective teaching through the problems of students, and finally how to achieve the purpose of improving the teaching effect. Through teaching practice, the author believes that wisdom test is an effective method. Through the analysis of the data provided in the wisdom test, problems in the learning process of students can be found, and macro and micro guidance can be provided to the teaching, helping to establish a scientific college English teaching model.